2016
DOI: 10.1002/art.39929
|View full text |Cite
|
Sign up to set email alerts
|

Cam Deformity and Acetabular Dysplasia as Risk Factors for Hip Osteoarthritis

Abstract: Objective. Cam deformity and acetabular dysplasia have been recognized as relevant risk factors for hip osteoarthritis (OA) in a few prospective studies with limited sample sizes. To date, however, no evidence is available from prospective studies regarding whether the magnitude of these associations differs according to sex, body mass index (BMI), and age.Methods. Participants in the Rotterdam Study cohort including men and women ages 55 years or older without OA at baseline (n 5 4,438) and a mean follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 32 publications
10
117
1
1
Order By: Relevance
“…In this study, we investigated the influence that Gdf5 and its broad regulatory domains have on hip morphology, in the context of shape parameters relevant to OA, DDH, and dislocation. We revealed that: (1) Gdf5 loss results in substantial dysmorphologies to the proximal femur and acetabulum in line with known features involved in hip instability, developmental dislocation, injury, and adult onset OA; (2) Compared to upstream regulatory sequences, downstream regulatory sequences of Gdf5/GDF5 drive stronger, more ubiquitous prenatal hip expression and uniquely control postnatal hip expression; (3) This regulatory structure is functionally important as downstream sequences were capable of restoring Gdf5 loss-of-function phenotypes to normal, a situation not observed when using the upstream region. These latter two findings have important ramifications to how we understand GDF5 and its association with OA and hip dysplasia/dislocation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this study, we investigated the influence that Gdf5 and its broad regulatory domains have on hip morphology, in the context of shape parameters relevant to OA, DDH, and dislocation. We revealed that: (1) Gdf5 loss results in substantial dysmorphologies to the proximal femur and acetabulum in line with known features involved in hip instability, developmental dislocation, injury, and adult onset OA; (2) Compared to upstream regulatory sequences, downstream regulatory sequences of Gdf5/GDF5 drive stronger, more ubiquitous prenatal hip expression and uniquely control postnatal hip expression; (3) This regulatory structure is functionally important as downstream sequences were capable of restoring Gdf5 loss-of-function phenotypes to normal, a situation not observed when using the upstream region. These latter two findings have important ramifications to how we understand GDF5 and its association with OA and hip dysplasia/dislocation.…”
Section: Discussionsupporting
confidence: 56%
“…(12-14, 16-18) These types of regulatory mutations often have less pleiotropic effects on phenotypes. For example, recent reports have shown substantial variations in these hip morphologic features between subjects with progressive hip OA and matched controls,(2, 23, 24) and candidate association and GWAS studies have repeatedly revealed the association of the GDF5 locus with OA, including that of the hip. In these studies, a large 130 kb haplotype underlies risk of OA at the locus.…”
Section: Discussionmentioning
confidence: 99%
“…There is also considerable interest in the role of shape abnormalities in hip OA, exemplified by cam‐type deformities caused by extra bone growth around the anterolateral aspect of the femoral head, leading to femoroacetabular impingement (FAI) , which are associated with premature onset of OA . In the Rotterdam Study, individuals with cam‐type deformity and acetabular dysplasia were reported to have an ~2‐fold increased risk of radiographic hip OA compared with controls .…”
mentioning
confidence: 99%
“…3 In contrast, it appears that the presence of a pincer deformity may have a protective effect against the development of OA. 3,73 Whether these findings can be extrapolated to athletes younger than 40 years of age is currently unknown. In older athletes, hip OA should always be considered and is clinically indicated by hip flexion of 115° or less and hip internal rotation less than 15°, and radiographically verified as joint space narrowing or presence of femoral or acetabular osteophytes.…”
Section: Imaging For Hip-related Groin Painmentioning
confidence: 99%